(untitled) (Indian Journal of Animal Production and Management, 2015)
A study was conducted on suckling behavior of 13 Gir calves of 0 to 15 days maintained at Kasturba Gandhi National Memorial Trust, Dairy Farm Kasturbagram Khandwa Road, Indore M.P.. The male calves required lesser attempt to teat seeking (6.11±0.86) as compared to female calves (11.77±0.82.). The male calves took longer duration (216.75±2.18 minutes) to hold the udder for first time than that of female calves (121.00±2.08) and lesser stroke for letting down of milk (1.86±0.35) than female ones (2.81±0.33times). The summer born calves searched the udder in lesser attempts (7.33±0.33) then those born in winter (10.54±0.78). The effect of suckling traits on growth rate up to 45 days of their life showed that it had significant effect on growth rate at 30th days of age and there is no significant effect had exert at 15th and 45th days of age of Gir calves.